Technological development of evaporative cooling systems and its integration with air dehumidification processes: A review - Abdullah, Shekh; Zubir, Mohd Nashrul Bin Mohd; Bin Muhamad, Mohd Ridha; Newaz, Kazi Md Salim; Öztop, Hakan Fehmi; Alam, Md Shadab; Shaikh, Kaleemullah (Elsevier Science Sa, 2023)
Internal space cooling technology is pushing toward promoting alternatives from conventional vapor compression systems to mitigate global warming. Many innovative cooling systems are currently focusing on Research and development (R&D) and commercialization. An evaporative cooling system is one of the possible solutions for vapor compression systems. Despite showing a promising alternative to vapor compression systems, their market penetration is insignificant in society. This stems from the challenges inherent within its operation in diverse climate conditions. In this critical review, various evaporative cooling systems along with their recent developments, were presented and discussed. In search of best outcome and limitation of evaporative cooling systems, a comparison of the performance of selected evaporative cooling system were discussed further. The current review also encapsulates the fundamentals and working principles of various dehumidification systems used in the industrial, residential, and agricultural sectors. Then, the solid and liquid desiccant dehumidification systems were further explored, and their effects on the evaporative cooling system were analyzed. Finally, the liquid desiccant and membrane dehumidification systems were comprehensibly reviewed with their effects on the evaporative cooling system. Based on the energy-saving potential analysis, it was found that independent dehumidification before cooling is an effective method to improve the efficacy of the evaporative cooling system in comparison to the conventional approach at different outdoor conditions. Also, an enhanced evaporative cooling system was found to be a promising replacement for vapor compression system. To provide thermal comfort in hot and humid conditions, membrane dehumidification with a dew point evaporative cooling system shows promise as a substitute air-cooling technology with reduced power usage. (c) 2023 Elsevier B.V. All rights reserved.
Keywords: Vapor compression system; Thermal comfort; Evaporative cooling system; Desiccant dehumidification; Membrane dehumidification; Enhanced evaporative cooling system